Clinical Significance of Sarcopenia among Patients with Advanced Oropharyngeal Cancer. (14th August 2018) - Tamaki, Akina; Manzoor, Nauman F.; Babajanian, Eric; Ascha, Mustafa; Rezaee, Rod; Zender, Chad A.
Abstract : Objectives: We investigated the prevalence and impact of sarcopenia on disease‐free survival (DFS) and overall survival (OS) in advanced oropharyngeal cancer. Study Design: Retrospective study. Setting: Single‐institution tertiary cancer care center. Subjects and Methods: We identified patients with advanced oropharyngeal cancer with pretreatment positron emission tomography–computed tomography scans for image analysis. Data were collected on the following variables: age, sex, smoking and alcohol status, stage (TNM and American Joint Committee on Cancer), human papillomavirus (HPV) status, body mass index (BMI), and treatment modality. Results: Of 113 patients identified with oropharyngeal cancer, 32 had sarcopenia: these patients were older (63.5 vs 57.6 years, P =. 01), were less likely to be male (53.1% vs 76.5%, P =. 03), and had a lower mean BMI (24.5 vs 28.4 kg/m 2, P =. 009). Eighty‐five subjects had HPV‐positive disease, and they had a higher BMI (28.2 vs 24.2 kg/m 2, P =. 01) than that of patients without HPV. Twenty‐one subjects who were HPV positive had less cancer recurrence (24.7% vs 48.1%, P =. 04) than that of their HPV‐negative counterparts. Log‐rank testing showed no difference in DFS ( P =. 06) associated with sarcopenia but a significant difference in OS ( P =. 049). There were differences in DFS ( P =. 009) and OS ( P =. 023) based on HPV status. According to univariable and multivariable models, HPV positivity exhibited improved DFS and OS. Sarcopenia was not statistically significant in survival models; however, it was associated with increased mortality and recurrence. Conclusion: Sarcopenia is a prognostic factor affecting OS independent of HPV status in advanced oropharyngeal cancer.